Evaluación de metales pesados e indicadores de contaminación en el puerto de paita (departamento de piura). - Cerna Villajulca, Diana Ivón (2013)
The Port of Paita, is located in the province of Paita to 57 km. of the city of Piura, in the department of the same name, geographical position is 81 ° 6'23 '', longitude 0 and 5 ° S latitude 5'28''8 northeastern end of Peru. In this thesis project it has evaluated the environmental deterioration of this port with respect to air, land and sea, carrying out physicochemical, these 3 resources analysis respectively. For air monitoring: Determination of Sediment, particulate matter and sulfur dioxide. For evaluation of soil: Determination of Chlorides and Nitrates. For evaluation of seawater: Determination of total solids, temperature, DO, BOD 5, COD, chlorides, pH, total coliform and heavy metals (Cd, Cu, Cr and Pb). Paita is considered as the axis of regional development of Piura concentrating activities such as the fishing industry, chemical manufacturing industries and national defense activities, but these activities are sources of pollution that cause the loss of biological, landscape and cultural diversity and deterioration quality of life of the population. Environmental conditions in the port of Paita indicate that the coastal waters are in the process of deterioration, according to the water law and additional rules given by various factors, also a deterioration of their physical and urban space is seen. a recovery plan whose purpose establish a plan for participatory environmental monitoring plan installation of technologies to recover liquid and solid waste from industrial and human activity and propose a plan of environmental awareness for the town of Paita arises.